LEVEL OF MILITARY THREATS IN REGIONAL AND THE NATIONAL DEFENSE BUDGET POLICY IN THE PERIOD OF 1990-2008 - Johnson Kennedy, Posma Sariguna (Universitas Kristen Indonesia, 2018)
This paper would like to see the government responds to the military threats that facing Indonesia from its strategic environment, through its defense budget policy. Single equation, formed to capture the military threats to national defense budget. The model developed are from Smith Military Demand Model. The estimation result is that the level of threat have influence on the defense budget. Indonesia must remain vigilant, because of the military rising of other countries. The strategic environment situation can be suddenly rise the escalation of threat.Keywords: International Economics, Defense Economics, Military Threats, Defense Budget.